Peningkatan Tingkat Kegemaran Membaca (TGM) Masyarakat Melalui Pengukuran Indeks Gemar Membaca (IGM) - Endang Fatmawati (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The key performance indicators of library affairs are carried out by measuring the culture of the people’s love of reading, related to the basis of program preparation, library development strategy, as well as the basis for preparing library policy directions. The high level of love for reading in the community has an impact on the level of welfare of the community. The phenomenon of people’s fondness for reading can be seen from the results of the study of their love of reading with their index value. To increase the love of reading, scientific research standards are needed which are the basis for making decisions or policies. Surveys must be in accordance with scientific principles so that research results can be justified. The high community literacy development index and the reading love index will realize a high community literacy index. Libraries can contribute in measuring the reading love level to measure the community’s reading fondness index, both nationally and regionally, in a comprehensive and precise manner. The results of the study of the level of interest in reading can be used as a reference and guide for the National Library of Indonesia, the provincial library service, as well as the regency/city library in making policy for programs to increase the love of reading for people throughout Indonesia.